MSME Management Strategies Anf Financial Management Via E-Commerce To Foster Smart Society In The Digital Age - Dikananda, Fatihanursari; Khotimah, Khusnul; Sadikin, Abdurrahman; Darma, Putri Ekawati (Jurnal Ekonomi, 2024)
In the digital era, e-commerce adoption is a potential solution for business and financial management for MSMEs. This research aims to develop strategies for managing MSMEs and finance through e-commerce to foster a smart society in the digital era. The method used is literature review, the results show that e-commerce can increase sales and operational efficiency of MSMEs, but its success is highly dependent on digital and financial literacy. MSMEs with good digital and financial literacy tend to be more successful in utilizing e-commerce. This research recommends improving digital and financial literacy through training, technological infrastructure support, collaboration with e-commerce platform providers, development of appropriate financial products and services, and regulations that support and protect MSMEs. With the right strategies, MSMEs can grow and contribute more to the national economy, as well as foster a smarter and more adaptive society in the digital era.